A review of 18p deletions. (6th August 2015) - Hasi‐Zogaj, Minire; Sebold, Courtney; Heard, Patricia; Carter, Erika; Soileau, Bridgette; Hill, Annice; Rupert, David; Perry, Brian; Atkinson, Sidney; O'Donnell, Louise; Gelfond, Jon; Lancaster, Jack; et al.
<x xml:space="preserve">Abstract</x> Since 18p‐ was first described in 1963, much progress has been made in our understanding of this classic deletion condition. We have been able to establish a fairly complete picture of the phenotype when the deletion breakpoint occurs at the centromere, and we are working to establish the phenotypic effects when each gene on 18p is hemizygous. Our aim is to provide genotype‐specific anticipatory guidance and recommendations to families with an 18p‐ diagnosis. In addition, establishing the molecular underpinnings of the condition will potentially suggest targets for molecular treatments. Thus, the next step is to establish the precise effects of specific gene deletions. As we look forward to deepening our understanding of 18p‐, our focus will continue to be on the establishment of robust genotype–phenotype correlations and the penetrance of these phenotypes. We will continue to follow our 18p‐ cohort closely as they age to determine the presence or absence of some of these diagnoses, including spinocerebellar ataxia (SCA), facioscapulohumeral muscular dystrophy (FSHD), and dystonia. We will also continue to refine the critical regions for other phenotypes as we enroll additional (hopefully informative) participants into the research study and as the mechanisms of the genes in these regions are elucidated. Mouse models will also be developed to further our understanding of the effects of hemizygosity as well as to serve as models for treatment development. © 2015 Wiley Periodicals, Inc.